Mark Maximising in a Context of Uncertain Contribution: - Penny Hart (Grounded Theory Review: An International Journal, 2017)
Graduates in the United Kingdom are expected to possess professional skills fitting them for a successful transition to paid work. Employers tend to value student attributes such as communication skills, initiative and the ability to work well with others. Assessed group work at university has been seen as a way of promoting these skills and qualities, however it is not always popular with students, who can experience problems when working together.